Advancing Applied Research in Conservation Criminology Through the Evaluation of Corruption Prevention, Enhancing Compliance, and Reducing Recidivism - Kahler, Jessica S.; Rivera, Joseph W.; Steele, Zachary T.; Morales-Giner, Pilar; Rivera, Christian J.; Ahossin, Carol F.; Kaur, Ashpreet; Episcopio-Sturgeon, Diane J. (Frontiers in Conservation Science, 2021)
Concomitant with an increase in the global illegal wildlife trade has been a substantial increase in research within traditional conservation-based sciences and conservation and green criminology. While the integration of criminological theories and methods into the wildlife conservation context has advanced our understanding of and practical responses to illegal wildlife trade, there remain discrepancies between the number of empirical versus conceptual studies and a disproportionate focus on a few select theories, geographical contexts, and taxonomic groups. We present three understudied or novel applications of criminology and criminal justice research within the fields of fisheries, forestry, and wildlife conservation. First, criminological research on the application of corruption prevention in combating the illegal wildlife trade. Corruption has increasingly been getting attention from the non-governmental sector (e.g., Targeting Natural Resource Corruption project); however, there has been limited research aimed at understanding institutional opportunity structures, local conceptualizations of corruption, and the corresponding prevention strategies within conservation contexts. Second, the preemptive application of compliance theories when designing and monitoring Community-Based Conservation (CBC) programs such as community forestry, non-timber forest products, and community patrol programs. Applying opportunity theory and social development strategies are two suggestions to improve the effectiveness of CBCs in forestry and beyond. Finally, a discussion on recidivism (i.e., repeat offending) and non-instrumental or novel responses, utilizing illegal fishing as a case study. We present two alternative methods to traditional forms of punishment: restorative justice and community-based approaches. Lastly, we will present a diversity of priority research agendas within each of these topics.